Assessment of double hole contrast detail phantom for image displacement evaluation - Pauzi, Nur Farahana; Abdul Majid, Zafri Azran; Sapuan, Abdul HaliM; Che Azemin, Mohd Zulfaezal; Junet, Laila Kalidah (Trans Tech Publications Ltd., Switzerland, 2014)
Contrast Detail phantom is used to evaluate the Contrast Detail performance of imaging system. The wall of drilled hole in commercial Contrast Detail phantom will give effect to the penetration of x-ray beam divergence to pass through the base of each hole. This effect will lead to false appearance of image but it does not visualised in the radiograph. In this study, a new design of Contrast Detail phantom’s hole has been developed. The hole feature differs from the current Contrast Detail phantom. The hole consists of combination of different hole's diameters, whereby the small hole diameter (3 mm) is placed on top of large hole diameter of different measurements (5 mm, 7 mm and 10 mm). The thickness of double hole acrylic blocks vary from 10 mm, 15 mm, 20 mm, 25 mm and 30 mm. A tiny size of iron which is used as an indicator was placed at the bottom of each holes. Results shows that, as the value of Source Image Distance (SID) values decrease from 2000 mm, 1800 mm, 1600 mm, 1400 mm, 1200 mm, 1000 mm to 800 mm, the size of upper hole image in different thickness of acrylic block increases from the original size (3mm). In different SID setting, variable acrylic block heights (10 mm, 15 mm, 20 mm, 25 mm and 30 mm) which are located at 100 mm from the center show that, the heighest acrylic block visualises the greatest image displacement. Image displacement which occurs due to magnification can be compensated by increasing the level of SID value and also by reducing the height of acrylic block. The increment in image displacement occurs when the hole is situated far from the center of x-ray beam. The new design of hole shows the effect of displacement of object from the x-ray focal length in a well manner.